Pengaruh Potensi Diri, Status Sosial Ekonomi Orang Tua dan Lingkungan Sosial Terhadap Minat Melanjutkan Pendidikanke Perguruan Tinggi Siswa Kelas XI SMA Negeri 8 Padang - cici yulihendri; syamwil syamwil (Universitas Negeri Padang, 2021)
The purpose of this research is to determine the level of influence between “Self Potential, Economic Condition’s of Parents and Social Environment” on interest in continuing to the university 11th students of SMA Negeri 8 Padang. The research is a quantitative descriptive study using data collected with questionnaires and documentation. The sample used in this study is 170 students using proportional random sampling technique from 360 population with error rate 5%. The result of research, show that there are significant influence from the “self potential, economic condition’s of parents and social environment” as simultaneous on interest in continuing to the university among 11th students of SMA Negeri 8 Padang 60,9% while 39,1% is influenced bu other variables. “Self Potential there is a significant influence on interest in continuing to the university, Economic Condition’s of Parents (Parental Education and Parents Income) is influential but not significant on interest in continuing to the university and social environment there is a significant influence on interest in continuing to the university 11th students of SMA Negeri 8 Padang”.Keywords : Self Potential, Economic Condition’s Of Parent, Social Environment and Interest in Continuing Education to Higher Education